Sleeping Beauty - "Cowley, Joy" (United Arab Emirates; SABIS, 2015)
Retells the Charles Perrault's version of Sleeping Beauty, in which a wicked fairy casts a spell that dooms a princess to sleep for one hundred years
Keywords: Fairy tales